Framing the world: Strategic narratives of foreign states in China’s mainstream media (1950–2019) - Zhicong Chen; Zhengyi Liang; Zhenyu Wang; Xinya Jiang; Cheng-Jun Wang (PLoS ONE, 2026)
This study investigates how mainstream Chinese media have portrayed foreign states over the past seven decades. While scholars have extensively studied foreign media portrayals of China, little systematic or longitudinal evidence exists on how China’s official party press frames the world across different countries and time periods. Using word embedding techniques, this study traces media representations of major foreign countries (N = 94) on People’s Daily (1950–2019). Results show that media favorability trends in the People’s Daily closely mirror major turning points in Chinese foreign policy. Regression analyses reveal that a country’s economic development, industrialization, and military capacity are major predictors of its media image, while the influence of economic factors shifted significantly over time. These patterns reflect broader geopolitical transformations and China’s evolving global orientation. The findings illuminate how computational approaches can recover the structural and strategic logics of state media framing, with implications for ongoing debates on narrative power, cultural influence, and China’s evolving role in the global information order.